Benefits of vasodilating beta-adrenoblockers for arterial hypertension treatment - V. B. Mychka (Кардиоваскулярная терапия и профилактика, 2012)
Antihypertensive medications of the same class could differ by their pharmacodynamic parameters, which substantially affects the longterm treatment results. Nebivolol is one of the modern, highly selective β-adrenoblockers (β-AB). It is characterised not only by high β1-selectivity, but also by additional vasodilating activity, due to increased nitric oxide synthesis and, hence, beneficial metabolic effects. The results of the original studies and the external evidence demonstrate metabolic neutrality of nebivolol, absence of substantial changes in thyroid hormone levels, and improvement in heart rate variability, electrophysiological myocardial parameters, QT interval duration, and cerebral perfusion. Nebivolol is effective and safe even in higher-risk patients with metabolic syndrome and Type 2 diabetes mellitus.